Culture, Society and Development: simplifying complexity - Castillo Ochoa, Manuel (2018)
This essay, based on research carried out by different authors, seeks to present a «matrix of cultural action» separating its various components and classifying them in their respective fields. Presents a general vision of what is happening in the cultural field, locating its main actors and performances. And doing so, it explores the specificities of the national culture and its interaction with cultural industries, and the consequences on the national society. Its basic objective is to achieve a conceptual tool to «simplify» the complex current cultural process.